Estudo taxonômico e ecológico dos Ichneumonidae (Hymenoptera, Ichneumonoidea) em área de mata atlântica em diferentes estágios sucessionais, no Parque Estadual da Serra Do Mar, São Luiz do Paraitinga, SP, Brasil - Melo, Ivy Frizo de (2015)
The Hymenoptera parasitoids have valuable ecological role as predators, pollinators, and parasitoids, being responsible for the natural control of populations of many phytophagous species. This paper aims to contribute to the increase in knowledge about taxonomy and geographical distribution of Ichneumonidae family in forest patches of tropical rainforest in different successional stages in Serra do Mar State Park, Santa Virgínia Center, São Luiz do Paraitinga, SP . The material was collected using Moericke traps in nine points, three in each area, degraded, secondary succession and preserved. The samples were collected every 30 days for 12 months. Data Loggers were used to obtain local abiotic variables information. Of the 19 identified subfamilies, Cryptinae, Ichneumoninae and Orthocentrinae were the most abundant and the only ones considered common, dominant and constant, while Ctenopelmatinae, Labeninae, and Lycorininae Ophioninae were considered rare. The preserved area had the highest abundance and lower richness. The highest richness, diversity and evenness were observed in degraded area, the lowest abundance and evenness in secondary succession area. The abundance's distribution of subfamilies showed a positive relationship between the dry and rainy seasons and the different successional stages. In degraded and secondary succession areas, there was no significance in the relationship between the variations of richness, abundance and diversity of Ichneumonidae’s subfamilies and abiotic variables. In preserved area, there was an indication of the relationship between measures of diversity and relative humidity. The Anomaloninae, Banchinae, Cremastinae, Ctenopelmatinae, Diplazontinae, Labeninae, Lycorininae, Mesochorinae, Metopiinae, Nesomesochorinae, Ophioninae, Pimplinae, Rhyssinae, Tersilochinae and Tryphoninae were identified in 72 species and morphospecies, divided into 32 genera, with 20 possible new species. Five genera and 22 species were reported for the first time to Brazil.